Low-carbon cementing material prepared from waste glass powder and preparation method of low-carbon cementing material

By combining waste glass powder with calcium-containing industrial solid waste and sulfates, low-carbon gelling materials are prepared, which solves the problem that waste glass powder and industrial solid waste cannot be used with high added value, and achieves the dual benefits of environmental protection and economic benefits.

CN119977458APending Publication Date: 2025-05-13JIAXING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510082359.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize waste glass powder and industrial solid waste, resulting in the inability to reuse these wastes with high added value, affecting environmental protection and economic benefits.

Method used

By combining waste glass powder with calcium-containing industrial solid waste and sulfates as excitants, low-carbon gelling materials with certain strength are prepared using equipment such as ball mills and mixers.

Benefits of technology

The high added value utilization of waste glass powder and industrial solid waste has been achieved. The prepared low-carbon gelling materials have good compressive strength and gelling properties, which can replace some cement and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119977458A_ABST
    Figure CN119977458A_ABST
Patent Text Reader

Abstract

The invention discloses a low-carbon cementing material prepared from waste glass powder, and relates to a cementing material for buildings, and the low-carbon cementing material is prepared from the following components in parts by weight: 40-60 parts of waste glass powder, 0-33 parts of Portland cement, 0-20 parts of desulfurized gypsum, 0-27 parts of superfine slag powder, 10-25 parts of calcium oxide, 33-42 parts of water and 0.5-1 part of a water reducing agent. According to the invention, the waste glass powder generated in the photovoltaic glass edging process is compounded with a certain amount of cement or calcium-containing industrial solid waste material, and then calcium hydroxide, sulfate and other excitants are used to prepare the cementing material with certain strength. The compressive strength of the prepared cementing material can reach 15 MPa or above in 7 days, the compressive strength of the cementing material can reach 32.5 MPa or above in 28 days, the initial setting time ranges from 54 min to 96 min, the final setting time ranges from 120 min to 230 min, the self-shrinkage value of the cementing material ranges from 30 mu epsilon to 62 mu epsilon in 28 days, the drying shrinkage value of the cementing material ranges from 130 mu epsilon to 340 mu epsilon in 90 days, and the water absorption ranges from 1.5% to 4.2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a green low-carbon cementitious material, and in particular to a low-carbon cementitious material prepared by utilizing waste glass powder and a preparation method thereof. Background Art

[0002] Glass is widely used in people's daily life. Compared with paper products and metal products, glass products have obvious advantages, such as high transparency, durability, good waterproofness and no rust. However, glassware and glass doors and windows are easy to break, and the output of broken glass is not low, which can be used as a recycled material for secondary use. Therefore, how to recycle waste glass to create better economic and environmental benefits has become a hot topic of current research.

[0003] Photovoltaic glass is a special glass that uses solar radiation to generate electricity. It is composed of glass, solar cells, films, back glass and special metal wires. The edges of finished photovoltaic glass products need to be polished with a grinding wheel. The diamond abrasive in the grinding wheel will be mixed with glass powder. Diamond abrasive cannot melt at a high temperature of 1500℃, so photovoltaic glass companies cannot process waste glass powder into transparent glass again. The current treatment method is mainly landfill. Anhui Xinyi Solar Energy Company has multiple production bases, generating 300-500 tons of waste glass powder every day. Landfill alone cannot solve the problem in the long term. The company urgently needs to reuse these waste glass powders and develop high value-added products to generate economic benefits. On the other hand, the industrial solid waste slag powder generated by the metallurgical industry and the industrial by-product desulfurization gypsum of thermal power plants need to be treated urgently. It is urgent to effectively combine the above industrial solid wastes and develop a low-carbon cementitious material with certain cementitious properties that is expected to replace high-energy consumption and high-emission cement.

[0004] For example, patent No. 202311166605.3, entitled A waste glass powder low-carbon cementitious material and its preparation method, the cementitious material is prepared using the following components: by mass: 80-120 parts of waste glass powder, 30-50 parts of sodium silicate solution, 6-10 parts of alkaline solution, the mass percentage of each oxide in the chemical composition of the waste glass powder is: SiO2 (71.10%), Na2O (13.56%), CaO (9.13%), Al2 O3 (2.32%), MgO (1.70%), K2O (1.06%) and others (1.13%); waste glass powder is ball milled for 10-30 minutes and then sieved to select powder with a particle size of less than 75μm; the chemical composition of sodium silicate solution accounts for 27.3% of SiO2, 8.54% of Na2O, and the modulus is 3.3; waste glass powder low-carbon cementitious material, the compressive strength can reach 50-95MPa after curing for 2-3 days. The Al and Ca contents in the waste glass powder components are low, so a large amount of alkali needs to be added, which increases the preparation cost, and the coagulation time is shortened, which is not conducive to construction operation, and ultimately leads to a great limitation of the scope of application. Summary of the invention

[0005] Based on the above description, the present invention proposes a method for preparing a low-carbon cementitious material using waste glass powder, wherein waste glass powder generated when polishing finished photovoltaic glass products is used as the main raw material, a small amount of calcium industrial solid waste is used as the auxiliary material, and an activator such as calcium hydroxide or sulfate is used to stimulate its activity to prepare a cementitious material with a certain strength. The present invention can absorb a large amount of industrial waste, realize the high added value utilization of industrial solid waste, and has great engineering practical significance for the development of circular economy.

[0006] The present invention is implemented by the following technical scheme: a low-carbon cementitious material prepared by using waste glass powder, using waste glass powder as raw material, calcium-containing industrial solid waste as auxiliary material, sulfate as activator, adding water reducing agent, to prepare the low-carbon cementitious material.

[0007] Furthermore, the waste glass powder is glass powder containing corundum particles produced in the photovoltaic glass edge grinding process, and the powder is a powder with a particle size of 400 mesh; the calcium-containing industrial solid waste is a by-product of the metallurgical industry, which is slag powder, calcium oxide and silicate cement; the sulfate uses the original desulfurized gypsum produced by the thermal power plant without calcination and treatment, and the main component is CaSO4·2H2O.

[0008] Furthermore, the water reducing agent is a polycarboxylic acid high-efficiency water reducing agent with a water reducing rate of 35%.

[0009] A low-carbon cementitious material prepared from waste glass powder consists of the following components in parts by weight: 40-60 parts of waste glass powder, 0-33 parts of Portland cement, 0-20 parts of desulfurized gypsum, 0-27 parts of slag powder, 10-25 parts of calcium oxide, 33-42 parts of water, and 0.5-1 part of a water reducing agent.

[0010] A method for preparing a low-carbon cementitious material using waste glass powder comprises the following steps:

[0011] 1) Grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0012] 2) According to the weight ratio, 40-60% of waste glass powder, 0-33% of silicate cement, 0-10% of desulfurized gypsum, 0-27% of slag powder, and 10-25% of calcium oxide are added to a planetary cement mortar mixer in sequence and stirred evenly. The mixture is stirred slowly for 25s-35s to obtain a powder. The stirring speed is 135-145r / min.

[0013] 3) Dissolve 0.5-1 of water reducer in 33-42 of water, add to the dry-mixed powder in the planetary cement mortar mixer in step 2), stir slowly for 60 seconds, and then stir quickly for 60 seconds to obtain a low-carbon cementitious material; the slow stirring speed is 135-145r / min, and the fast stirring speed is 175-195r / min;

[0014] The compressive strength of low-carbon cementitious materials is above 15MPa after 7 days and above 32.5MPa after 28 days; the initial setting time is 54-96min and the final setting time is 120-230min; the autogenous shrinkage value after 28 days is 30-62με and the drying shrinkage value after 90 days is 130-340με, and the water absorption rate is 1.5-4.2%.

[0015] The alkali excitation mechanism is to add alkaline substances such as sodium silicate or sodium hydroxide to excite silica-alumina or calcium-silica-alumina minerals, so that their Si-O or Al-O bonds are destroyed and then repolymerized to form hydrated calcium silicate (alumina) (C-(A)-SH) gel or hydration (NASH), thereby producing gelling properties. If sodium silicate solution is used to excite waste glass powder, a very small amount of gelling material will be generated due to the lack of Al and Ca components. The Al and Ca components in the glass powder itself are not high, so the excitation effect is not obvious. Conversely, the sodium silicate component in the waste glass powder can be used as an alkali excitation component to excite the activity of calcium minerals and produce gelling properties.

[0016] The present invention can not only realize the high added value utilization of waste glass powder, but also absorb a large amount of industrial solid byproducts and waste, minimize the pollution and emission of urban solid waste to the environment, and comply with the principle of sustainable development of environment and resources. The preparation process of the low-carbon cementitious material involved in the present invention is energy-saving and environmentally friendly, and can replace cement as a cementitious material to a certain extent, with excellent performance and broad development prospects.

[0017] Waste glass powder itself does not have gelling properties, and its large amount of siliceous components have potential activity. Only by using an effective stimulant to stimulate its activity can it produce gelling properties, thereby realizing its reuse value. The present invention uses calcium-containing solid waste or sulfate to stimulate the activity of waste glass powder. Calcium-containing industrial solid waste mainly includes slag powder, calcium oxide, and cement, which are by-products of the metallurgical industry. Sulfate mainly uses desulfurized gypsum, a solid waste generated after the flue gas desulfurization project is implemented in thermal power plants, and its main component is CaSO4·2H2O. Ca in calcium-containing solid waste can react with silicon-aluminum components in waste glass powder to generate C-(A)-SH gel and calcium hydroxide and other products that can develop strength; desulfurized gypsum can react with silicon-aluminum components in waste glass powder to generate hydrated calcium silicate gel and calcium sulfonite crystals. After being stimulated by calcium-containing solid waste or sulfate, the microstructure of the cementitious material prepared from waste glass powder is uniform and dense. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a comparison of the morphology of the sample at 28 days of age before and after excitation of waste glass powder;

[0019] Figure 2 This is the XRD spectrum of waste glass before and after excitation. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is described in detail below. The technical solution is only a preferred implementation of the present invention. It should be noted that: without departing from the principle of the present invention, those skilled in the art may also make several improvements and modifications, which should also be considered as the protection scope of the present invention.

[0021] Example 1

[0022] A low-carbon cementitious material prepared from waste glass powder is prepared according to the following weight percentages: 50% waste glass powder, 27% silicate cement, 23% calcium oxide, and 0.5w / w% water reducer; the water reducer is a polycarboxylic acid-based high-efficiency water reducer.

[0023] The preparation method is as follows:

[0024] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0025] 2) Add 50% of waste glass powder, 27% of silicate cement and 23% of calcium oxide into a planetary cement mortar mixer in a certain weight ratio and mix them evenly at 130 rpm for 30 seconds to obtain powder;

[0026] 3) Add 0.5% water reducing agent dissolved in 35% water to the dry-mixed powder in the planetary cement mortar mixer in step 2), stir at 130r / min for 60s, and then stir rapidly for 60s to obtain a green low-carbon cementitious material.

[0027] After testing, the prepared low-carbon cementitious material has a compressive strength of 18.2MPa in 7 days and 33MPa in 28 days. The initial setting time is 54min, the final setting time is 150min, the 28-day autogenous shrinkage value is 42με, the 90-day drying shrinkage value is 210με, and the water absorption rate is 2.3%.

[0028] Example 2

[0029] A low-carbon cementitious material prepared from waste glass powder is prepared according to the following weight percentages: 60% waste glass powder, 27% slag powder, 13% calcium oxide, and 0.5w / w% water reducer, wherein the water reducer is a polycarboxylic acid-based high-efficiency water reducer.

[0030] The preparation method is as follows:

[0031] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0032] 2) According to the weight ratio, 60% of waste glass powder, 27% of slag powder and 13% of calcium oxide are added into a planetary cement mortar mixer and stirred evenly at 130r / min for 30s;

[0033] 3) Add 0.5% water reducing agent dissolved in 38% water to the dry-mixed powder in the planetary cement mortar mixer in step 2), stir at 130r / min for 60s, and then stir at 280r / min for 60s to obtain a green low-carbon cementitious material.

[0034] After testing, the prepared low-carbon material has a compressive strength of 25.2MPa in 7 days and 43MPa in 28 days. The initial setting time is 65min, the final setting time is 190min, the 28-day autogenous shrinkage value is 62με, the 90-day drying shrinkage value is 160με, and the water absorption rate is 2.1%.

[0035] Example 3

[0036] A low-carbon cementitious material prepared from waste glass powder is prepared according to the following weight parts: 40% waste glass powder, 40% slag powder, 20% calcium oxide, and 0.8w / w% water reducer. The water reducer is a polycarboxylic acid-based high-efficiency water reducer.

[0037] The preparation method is as follows:

[0038] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0039] 2) According to the weight ratio, 40 parts of waste glass powder, 40 parts of slag powder and 20 parts of calcium oxide are added into a planetary cement mortar mixer and stirred evenly at 130 r / min for 30 seconds;

[0040] 3) Add 0.8% water reducing agent dissolved in 40% water to the dry-mixed powder in the planetary cement mortar mixer in step 2), stir at 130r / min for 60s, and then stir at 280r / min for 60s to obtain a green low-carbon cementitious material.

[0041] After testing, the prepared green and low-carbon material has a compressive strength of 20.1MPa in 7 days and 36.5MPa in 28 days. The initial setting time is 92min, the final setting time is 96min, the 28-day autogenous shrinkage value is 62με, the 90-day drying shrinkage value is 340με, and the water absorption rate is 1.5%.

[0042] Example 4

[0043] A low-carbon cementitious material prepared from waste glass powder is prepared according to the following weight proportions: 55% waste glass powder, 23% silicate cement, 12% calcium oxide, 10% desulfurized gypsum, and 0.5% water reducing agent, wherein the water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

[0044] The preparation method is as follows:

[0045] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0046] 2) Add 55% of waste glass powder, 23% of Portland cement, 12% of calcium oxide, and 10% of desulfurized gypsum into a planetary cement mortar mixer and mix evenly at 130r / min for 30s;

[0047] 3) Add 1.0% water-reducing agent dissolved in 42% water to the dry-mixed powder in the planetary cement mortar mixer in step 2), stir at 130r / min for 60s, and then stir at 280r / min for 60s to obtain a green low-carbon cementitious material.

[0048] After testing, the prepared green and low-carbon material has a compressive strength of 23.6MPa in 7 days and 40.6MPa in 28 days. The initial setting time is 96min, the final setting time is 230min, the 28-day autogenous shrinkage value is 30με, the 90-day drying shrinkage value is 130με, and the water absorption rate is 4.2%.

[0049] Comparative Example 1

[0050] The cementitious material is prepared according to the following weight proportions: 100% of waste glass powder and 0.5w / w% of water reducing agent. The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

[0051] The preparation method is as follows:

[0052] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0053] 2) Add 100 parts of waste glass powder into a planetary cement mortar mixer and mix evenly, slowly mixing for about 30 seconds;

[0054] 3) Add 0.5% water reducer dissolved in 35% water into a planetary cement mortar mixer, stir slowly for 60 seconds, and then stir quickly for 60 seconds.

[0055] After testing, it was found that the waste glass powder slurry produced did not coagulate and have adhesive properties for a long time, did not have the basic properties of cementitious materials, and could not be used in building materials related industries.

[0056] Comparative Example 2

[0057] The cementitious material is prepared according to the following weight proportions: 80% of waste glass powder, 20% of silicate cement, and 0.5w / w% of water reducing agent. The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

[0058] The preparation method is as follows:

[0059] 1) grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill;

[0060] 2) Add 80% of waste glass powder and 20% of silicate cement into a planetary cement mortar mixer and mix evenly for about 30 seconds;

[0061] 3) Add 0.5% water reducer dissolved in 38% water to the dry-mixed powder in the planetary cement mortar mixer, stir slowly for 60 seconds, and then stir quickly for 60 seconds.

[0062] According to tests, the prepared cementitious material can only solidify after 72 hours, the compressive strength cannot be measured after 7 days, and the compressive strength after 28 days is 1.2MPa. The cementitious properties are poor and cannot be used in building materials related industries.

[0063] like Figure 1 As shown in Figure 2, Ca in calcium-containing solid waste can react with the silicon-aluminum components in waste glass powder to generate C-(A)-SH gel and calcium hydroxide and other products that can develop strength, see Figure 1 (b); Desulfurized gypsum can react with the silicon-aluminum components in the glass powder to form hydrated calcium silicate gel and ettringite crystals, see Figure 1 (c) By Figure 1 It can also be seen that after being stimulated by calcium-containing solid waste or sulfate, the microstructure of the cementitious material prepared by waste glass powder is uniform and dense, which is different from the unstimulated granular microstructure ( Figure 1 (a)) is in sharp contrast.

[0064] In order to further determine the changes in the phase composition of the waste glass powder before and after activation, the present invention conducted an X-ray diffraction analysis (XRD), and the results are shown in Figure 2 As can be seen from the figure, the unexcited waste glass powder is in an amorphous state without any product peaks ( Figure 2 (a)), macroscopically, it shows no gelling properties; after activation, the samples detected calcium silicate hydrate gel (Calcium Silicate Hydrate), calcium hydroxide (Portlandite) and ettringite (Ettringite) and other gelling phases and crystal phases that are beneficial to the development of strength ( Figure 2 (b)), which is manifested in the macro sense as a continuous increase in intensity.

[0065] In summary, the implementation of the present invention effectively stimulates the potential gelling properties of waste glass powder, develops a green and low-carbon gelling material, turns waste into treasure, and conforms to the concept of sustainable development. The green and low-carbon gelling material can be applied to the low-strength cement concrete products industry, road materials and other fields, helping the building materials industry to achieve the "dual carbon" goal as soon as possible.

Claims

1. A low-carbon cementitious material prepared from waste glass powder, characterized in that: Low-carbon cementitious material is prepared by taking waste glass powder as raw material, calcium-containing industrial solid waste as auxiliary material, sulfate as activator and adding water reducing agent.

2. The low-carbon cementitious material prepared from waste glass powder according to claim 1, characterized in that The waste glass powder is glass powder containing corundum particles produced in the photovoltaic glass edge grinding process, and the powder is a powder with a particle size of 400 meshes; the calcium-containing industrial solid waste is a by-product of the metallurgical industry, which is slag powder, calcium oxide and silicate cement; the sulfate adopts the original desulfurized gypsum produced by the thermal power plant without calcination and treatment, and the main component is CaSO4·2H2O.

3. The low-carbon cementitious material prepared from waste glass powder according to claim 1, characterized in that The water reducing agent is a polycarboxylic acid high efficiency water reducing agent with a water reducing rate of 35%.

4. A low-carbon cementitious material prepared from waste glass powder according to claims 1 to 3, characterized in that: The invention is composed of the following components in parts by weight: 40-60 parts of waste glass powder, 0-33 parts of silicate cement, 0-20 parts of desulfurized gypsum, 0-27 parts of slag powder, 10-25 parts of calcium oxide, 33-42 parts of water and 0.5-1 parts of water reducing agent.

5. A method for preparing a low-carbon cementitious material using waste glass powder, using the low-carbon cementitious material prepared using waste glass powder as claimed in claims 1 to 4, characterized in that: The following steps are involved: 1) Grinding the waste photovoltaic glass powder into a powder material with a particle size of 400 meshes by a ball mill; 2) According to the weight ratio, 40-60% of waste glass powder, 0-33% of silicate cement, 0-10% of desulfurized gypsum, 0-27% of slag powder, and 10-25% of calcium oxide are added to a planetary cement mortar mixer in sequence, and stirred evenly, and stirred slowly for 25s-35s to obtain powder; 3) Dissolve 0.5-1 part of water reducer in 33-42 part of water, add the mixture into the dry-mixed powder in the planetary cement mortar mixer in step 2), stir slowly for 60 seconds, and then stir quickly for 60 seconds to obtain low-carbon cementitious material.

6. The method for preparing low-carbon cementitious material using waste glass powder according to claim 5, characterized in that The low-carbon cementitious material has a 7-day compressive strength of more than 15 MPa and a 28-day compressive strength of more than 32.5 MPa; an initial setting time of 54 to 96 minutes and a final setting time of 120 to 230 minutes; a 28-day autogenous shrinkage value of 30 to 62 με, a 90-day drying shrinkage value of 130 to 340 με, and a water absorption rate of 1.5 to 4.2%.

Citation Information

Patent Citations

  • Waste glass powder low-carbon cementing material and preparation method thereof

    CN117247241A